Inhomogeneous structure of magnetic layer of the Kuril Island Arc - N. A. Palshin; A. N. Ivanenko; D. A. Alekseev (Геодинамика и тектонофизика)
An innovative technology of anomalous magnetic field inversion was applied to construct 2D models of the magnetic layer using three profiles crossing the southern, central and northern parts of the Kuril Island Arc. In the frontal area of the northern and southern parts, a zone of increased effective magnetization is clearly distinguished. In the central part of the island arc, increased magnetization is much less pronounced. Anomalous zones of positive effective magnetization have a deep part, the so-called "serpentinite wedge". The inhomogeneous lateral structure of the magnetic layer of the Kuril Island Arc suggests differences in the fluid regime and is reflected in the distribution of modern seismicity.